PENGARUH PEMBELAJARAN KOLABORATIF BERBANTUAN WORDWALL TERHADAP KETERAMPILAN MEMBACA TEKS NARASI SISWA - Maulana Adi Nugroho; Sari Yustiana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This study examines the effect of collaborative learning assisted by Wordwall on third grade students' narrative reading skills and reading comprehension. The research was conducted because preliminary classroom observations showed that students often struggled to read narrative texts fluently, identify important information, and explain the message of a story. A quantitative pre-experimental approach with a one group pre-test and post-test design was applied to 30 students at SD Negeri 1 Wonoagung. Data were collected through a reading performance rubric and a narrative comprehension test. The instruments were validated and then analyzed through descriptive statistics, normality testing, and paired sample t-test using SPSS. The results showed that the mean score increased from 39.40 in the pre-test to 74.75 in the post-test. The paired sample t-test produced p < .001, indicating a significant difference after treatment. These findings suggest that collaborative learning supported by Wordwall can create a more active, interactive, and meaningful reading class for elementary students.